2012
DOI: 10.1111/acer.12007
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Efficacy as a Predictor of Outcome After Residential Treatment Programs for Alcohol Dependence: Simply Ask the Patient One Question!

Abstract: General self-efficacy, that is, the patients' own prognosis of his success in remaining abstinent, was a central variable in predicting residential alcohol dependence treatment outcome. Self-efficacy showed a more accurate prognosis of outcome when it was assessed with just 1 question, than when assessed with the SCQ. With this simplified assessment, knowledge of the prognostic value of self-efficacy could be made applicable for everyday practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
41
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 22 publications
4
41
0
1
Order By: Relevance
“…Many participants specifically referenced internal motivation as the primary or only component that predicts successful drug treatment. This is consistent with published data on the motivations of drug treatment seeking and completion behavior among diverse groups of substance users (Johansen, Brendryen, Darnell, & Wennesland, 2013; Kelly & Greene, 2014; Ludwig, Tadayon-Manssuri, Strik, & Moggi, 2013; Murphy, Bentall, Ryley, & Ralley, 2003). For some participants, however, involvement in the criminal justice system interrupted their usual pattern of drug use.…”
Section: Discussionsupporting
confidence: 92%
“…Many participants specifically referenced internal motivation as the primary or only component that predicts successful drug treatment. This is consistent with published data on the motivations of drug treatment seeking and completion behavior among diverse groups of substance users (Johansen, Brendryen, Darnell, & Wennesland, 2013; Kelly & Greene, 2014; Ludwig, Tadayon-Manssuri, Strik, & Moggi, 2013; Murphy, Bentall, Ryley, & Ralley, 2003). For some participants, however, involvement in the criminal justice system interrupted their usual pattern of drug use.…”
Section: Discussionsupporting
confidence: 92%
“…Support for this can be observed with generic, non-drug (general) self-efficacy being highly associated with substance use (46). Front line treatments for cannabis use disorders that hold strongest evidence for efficacy include Cognitive-Behavioral Therapy (CBT), MI, and Contingency Management (CM) (47).…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, a number of treatment outcome studies have shown that self-reported confidence in one's ability to maintain abstinence (self-efficacy) is associated with better treatment outcome (Dolan et al, 2008; Ludwig et al, 2013; Vielva and Iraurgi, 2001); however, much like studies of craving and longer-term outcomes, this finding is not always consistent (Demmel et al, 2006). Similar to cue-induced craving, self-efficacy may also be a better predictor of the likelihood of proximal use (Barta et al, 2009; Gwaltney et al, 2005).…”
Section: Discussionmentioning
confidence: 99%